DIFFICULTY OF ACCESS TO DRINKING WATER AND STATE OF HEALTH OF THE POPULATIONS OF GLAZOUÉ IN BENIN - BABADJIDE, CHARLES LAMBERT (My University, 2020)
Drinking water is a basic resource for all living things. Its quality influences the life of living beings. The present research aims to analyze the difficulties linked to access to drinking water in the municipality of Glazoué and the state of health of the populations.The methodological approach used consisted in using documentary research techniques, interviews, observation, analysis of the water collected and compared with WHO standards. For this research of a mixed nature, 110 actors were surveys, 4 water sources analyzed and statistics of water sick people collected. The data were processed and analyzed by comparison and the PEIR analysis model made it possible to analyze the harmful effects caused by the consumption of unhealthy water on a predominantly rural population with low and limited income with its socio-economic consequences.The populations of Glazoué are confronted with a water deficit in this case during the dry season. The majority of wells dry up during the dry season and thus expose populations to the risk of water contamination due to the fact that the water from these types of wells is filled with sand and microorganisms. As for modern wells and boreholes, poor management is the main cause of their abandonment. Any situation that predisposes people to resort to water sources of questionable quality that endanger their health.
Keywords: Glazoué; Drinking Water; Difficulty Of; Access; Population Health